2006
DOI: 10.1590/s0037-86822006000100019
|View full text |Cite
|
Sign up to set email alerts
|

Infecção natural de Triatoma vitticeps (Stal, 1859) por flagelados morfologicamente semelhantes a Trypanosoma cruzi (Chagas, 1909) no Estado do Espírito Santo

Abstract: Espécimes adultos de Triatoma vitticeps são capturados freqüentemente por moradores em áreas rurais do Estado do Espírito Santo, Brasil. Com o objetivo de determinar o índice de infecção natural desta espécie, examinamos os dejetos de 116 espécimes silvestres, capturados em 27 municípios do estado, após repasto sanguíneo em ave e dejeção espontânea. Destes, 100 (86,2%) estavam infectados por flagelados morfologicamente semelhantes a Trypanosoma cruzi. Detectamos índices de infecção natural de Tritoma vitticeps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…However, despite degradation, six different mammal species were captured, indicating that the area contains a moderate diversity of small wild mammal species. It has been reported that T. vitticeps presents high T. cruzi infection rates (more than 60 % of the triatomines are infected) [30, 117, 118]. The absence of positive hemocultures and borderline serological titers showed that the animals examined presented low force of infection and strongly suggests that triatomines are not being infected in the peridomicile area but in distant forest fragments.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, despite degradation, six different mammal species were captured, indicating that the area contains a moderate diversity of small wild mammal species. It has been reported that T. vitticeps presents high T. cruzi infection rates (more than 60 % of the triatomines are infected) [30, 117, 118]. The absence of positive hemocultures and borderline serological titers showed that the animals examined presented low force of infection and strongly suggests that triatomines are not being infected in the peridomicile area but in distant forest fragments.…”
Section: Discussionmentioning
confidence: 96%
“…Triatoma vitticeps is the more prevalent species in ES and can be found in Rio de Janeiro, Minas Gerais and Bahia states [27, 28]. Triatoma vitticeps occasionally forms colonies associated with opossum nests in peridomiciles and has high infection rates by flagellates, such as T. cruzi [29, 30]. In a study conducted between 2010 and 2012 (Dario, unpublished data), 55  T. cruzi isolates derived from T. vitticeps and P. geniculatus collected in ES subjected to molecular characterization, demonstrated the transmission of four T. cruzi DTUs (TcI, TcII, TcIII and TcIV).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the high dispersion capacity of T. vitticeps, primarily in the States of Espírito Santo, Minas Gerais, Rio de Janeiro and Bahia [22][23][24] . Other authors have confi rmed high rates of natural infection with T. cruzi, with a rate of positivity between 25% and 65% of insects examined [24][25][26][27] . Curiously, in the State of Espírito Santo where the frequency of T. vitticeps and positivity for T. cruzi is higher in rural dwellings, the prevalence of Chagas disease is low and limited to autochthonous cases of transmission by this species 28 .…”
Section: Epidemiological Evaluationmentioning
confidence: 99%
“…It is essentially a forest species, whose adults invade houses attracted by light or in search of blood meals, although they are apparently unable to colonize human habitations (Santos et al 2005). In Espírito Santo, insects captured indoors present high rates of infection by flagellates morphologically similar to Trypanosoma cruzi (Chagas, 1911) (Sessa & Carias 1986, Dias et al 1989, Santos et al 2006.Among the characteristics that define the capacity of a triatomine to infect a host with T. cruzi are feeding and defecation behavior. Species that defecate during or shortly after taking a bloodmeal, so that infected faeces are deposited on the host, show the greatest vector potential (Dias 1956, Diotaiuti et al 1995.…”
mentioning
confidence: 99%
“…It is essentially a forest species, whose adults invade houses attracted by light or in search of blood meals, although they are apparently unable to colonize human habitations (Santos et al 2005). In Espírito Santo, insects captured indoors present high rates of infection by flagellates morphologically similar to Trypanosoma cruzi (Chagas, 1911) (Sessa & Carias 1986, Dias et al 1989, Santos et al 2006.…”
mentioning
confidence: 99%